Side Lobe Lowered Novel Axially Displaced Ellipse Antenna Design for Radio Link System Compliant with ETSI EN 302 217-4-2 Class 3 - Tulum, Mehmet Akif; Turk, Ahmet Serdar (IEEE, 2021)
In this paper, an innovative Axially Displaced Ellipse (ADE) structure is introduced to improve the side and back lobe levels of high-gain Cassegrain reflector to comply with ETSI EN 302 217-4 Class-3 standards for radio link antennas. The operation frequency of Ku-band radio link antenna is between 12.7-13.3 GHz and the reflector diameter is 60 cm. ADE type reflector antennas provide high aperture efficiency by using dual reflectors on the antenna geometry. Typical ADE Antennas consist of main reflector, sub-reflector and feeder. To obtain suppressed back and side lobe levels, we firstly extended the corners of the reflector antenna and added an absorber to the extended area to reduce the diffraction from the corner points. Moreover, as the innovative aspect of this study, we proposed a corrugated structure on the sub-reflector. In this way, we maintained the aperture efficiency of the antenna and achieved improved low side and back lobe levels. The ADE antenna in accordance with ETSI EN 302 217-4 Class-3 standard was produced and measured in an anechoic chamber. The gain of the antenna is 35.8 dBi and the pattern complies with the ETSI EN 302 217-4 Class-3 standard.
Keywords: ADE antenna; radio link; ETSI standard; sub-reflector corrugated; side lobe suppression; DUAL-REFLECTOR ANTENNAS; COMBINATIONS; CASSEGRAIN; Engineering; Telecommunications